2020
DOI: 10.1007/s11356-020-09103-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Chlorella vulgaris and Nannochloropsis salina for nutrient and organic matter removal from municipal wastewater reverse osmosis concentrate

Abstract: Municipal wastewater reverse osmosis concentrate (ROC) poses health and environmental risks on its disposal as it contains nutrients and harmful organic compounds at elevated concentrations. This study compared a freshwater microalga Chlorella vulgaris and a marine microalga Nannochloropsis salina in suspended and alginate-immobilised cultures for batch and semicontinuous treatment of the ROC. The immobilised algae gave comparable nutrient removal rates to the suspended cells, demonstrating immobilisation had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Single-cell green microalgae such as Chlorella and Scenedesmus can grow well in wastewater, and are typically the dominant microalgal species in high rate algal ponds (Wollmann et al, 2019). Few species within these genera have been reported as effective for ROC treatment , and in our recent study, Chlorella vulgaris and the marine alga Nannochloropsis salina showed comparatively efficient nutrient removal from a municipal wastewater ROC (Mohseni et al, 2020). However, no systematic studies for identifying the species suitable for achieving the management objectives from a larger number of possible microalgae have been documented.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Single-cell green microalgae such as Chlorella and Scenedesmus can grow well in wastewater, and are typically the dominant microalgal species in high rate algal ponds (Wollmann et al, 2019). Few species within these genera have been reported as effective for ROC treatment , and in our recent study, Chlorella vulgaris and the marine alga Nannochloropsis salina showed comparatively efficient nutrient removal from a municipal wastewater ROC (Mohseni et al, 2020). However, no systematic studies for identifying the species suitable for achieving the management objectives from a larger number of possible microalgae have been documented.…”
Section: Introductionmentioning
confidence: 81%
“…Increasing alkalinity to 400 mg/L resulted in algal growth improvement and thus better DOC removal; however, with further increase in alkalinity level (i.e., 600 mg/L), DOC consumption subsequently decreased (Figure 4.8b). The DOC removal rate could be predicted by the empirical model developed (Equation 4.8) with some moderate deviations on testing it against experimental data reported in Mohseni et al (2020) for DOC removal rates of C. vulgaris and N. salina in ROC treatment (MAD of <24%, R 2 =0.86).…”
Section: Total Phosphorus Removalmentioning
confidence: 96%
See 1 more Smart Citation
“…The composition of municipal wastewater varies greatly because of the substances from various families, businesses, and institutions. For example, the COD and TN in a municipal sludge digestate were 2175 mg L −1 and 840 mg L −1 , and 164 mg L −1 and 43.2 mg L −1 [84], in municipalities with reserve osmosis concentrate [85], respectively. Generally, the COD, TN, and TP utilization efficiencies of municipal wastewater in microalgal Chlorella cultivation were approximately 85-100%, 80-100%, and 90-100%, respectively (Table 3).…”
Section: Municipal Wastewatermentioning
confidence: 99%
“…oculata, C. vulgaris, Nannochloropsis salina, Rhodomonas salina and so forth. [3][4][5] and wastewater as well that is, Chlorella sorokiniana, Micractiniumpusillum, Chlorella variabilis and so forth. 6 Surrounding environment (pH, temperature, presence of different salts) of microalgae exert significant effect on its biological pathways that lead to the synthesis of the different metabolites.…”
mentioning
confidence: 99%